answersLogoWhite

0


Best Answer

The index laws state that (an)m = an*m. Thus, (31/2)2 = 31 = 3.

User Avatar

Wiki User

āˆ™ 13y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

āˆ™ 12y ago

8

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is 3 square root 2?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Square root 2 times square root 3 times square root 8?

square root 2 times square root 3 times square root 8


What is 3 times 3 square root 2?

3(3 square root of 2) = 9(square root of 2)


Can 2 divided by 2 square root 3 be simplified?

Yes, the expression 2 divided by 2 square root 3 can be simplified. To simplify this expression, we need to rationalize the denominator. Multiplying both the numerator and the denominator by the conjugate of the denominator (2 square root 3), we get (2 * 2 square root 3) / (2 * 2 square root 3 * 2 square root 3). This simplifies to 4 square root 3 / 12, which further simplifies to square root 3 / 3.


What is the square root of 2 3 and 4?

1.4142135 is the square root of 2 1.7320508 is the square root of 3 2.0000000 is the square root of 4


What is the square root of 3 divided by 2 plus the square root of 3 divided by 2?

2 times the Square root of 3 + 4


Simplify the expression 2 square root 3 multiply square root 12?

hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)


5 square root of 3 2 square root of 3?

Square root of 6


Square root of 12 over the square root of 4?

2 root 3 over 2, so square root of 3


Square root of 18 in radical form?

the square root of 18 can be simplified to 3 * the square root of 2.The perfect square 9 is a factor of 18. That means the square root of 9 * the square root of 2 = the square root of 18.the square root of 9 can be simplified to 3.That leaves 3 * the square root of 2.


What is Square root of 3 plus square root of 3?

sqrt(3) + sqrt(3) = 2*sqrt(3) NOT sqrt(3 + 2)


Find the two numbers whose product is 1 and whose sum is 1?

x + y = 1xy = 1y = 1 - xx(1 - x) = 1x - x^2 = 1-x^2 + x - 1 = 0 or multiplying all terms by -1;(-x^2)(-1) + (x)(-1) - (1)(-1) = 0x^2 - x + 1 = 0The roots are complex numbers. Use the quadratic formula and find them:a = 1, b = -1, and c = 1x = [-b + square root of (b^2 - (4)(a)(c)]/2a orx = [-b - square root of (b^2 - (4)(a)(c)]/2aSox = [-(-1) + square root of ((-1)^2 - (4)(1)(1)]/2(1)x = [1 + square root of (1 - 4]/2x = [1 + square root of (- 3)]/2 orx = [1 + square root of (-1 )(3)]/2; substitute (-1) = i^2;x = [1 + square root of (i^2 )(3)]/2x = [1 + (square root of 3)i]/2x = 1/2 + [i(square root of 3]/2 andx = 1/2 - [i(square root of 3)]/2Since we have two values for x, we will find also two values for yy = 1 - xy = 1 - [1/2 + (i(square root of 3))/2]y = 1 - 1/2 - [i(square root of 3)]/2y = 1/2 - [i(square root of 3)]/2 andy = 1 - [1/2 - (i(square root of 3))/2)]y = 1 - 1/2 + [i(square root of 3))/2]y = 1/2 + [i(square root of 3)]/2Thus, these numbers are:1. x = 1/2 + [i(square root of 3)]/2 and y = 1/2 - [i(square root of 3)]/22. x = 1/2 - [i(square root of 3)]/2 and y = 1/2 + [i(square root of 3)]/2Let's check this:x + y = 11/2 + [i(square root of 3)]/2 +1/2 - [i(square root of 3)]/2 = 1/2 + 1/2 = 1xy = 1[1/2 + [i(square root of 3)]/2] [1/2 - [i(square root of 3)]/2]= (1/2)(1/2) -(1/2)[i(square root of 3)]/2] + [i(square root of 3)]/2](1/2) - [i(square root of 3)]/2] [i(square root of 3)]/2]= 1/4 - [i(square root of 3)]/4 + [i(square root of 3)]/4 - (3i^2)/4; substitute ( i^2)=-1:= 1/4 - [(3)(-1)]/4= 1/4 + 3/4= 4/4=1In the same way we check and two other values of x and y.


Multiply square root 3 by square root 2?

square root 6